2006
DOI: 10.1002/cbdv.200690114
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 4/5‐Deoxy‐4/5‐nucleobase Derivatives of 3‐O‐Methyl‐Dchiro‐inositol as Potential Antiviral Agents

Abstract: Using D-pinitol (= 3-O-methyl-D-chiro-inositol) as starting material, a concise synthesis of 4/5-deoxy-4/5-nucleobase derivatives 11-19 has been achieved. The key intermediate 9 was obtained in good yield via an epoxidation from mono-methanesulfonate of D-pinitol. The process of opening of the epoxide ring in 9 by nucleobases appeared to be regioselective in presence of 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU). All the synthesized carbocyclic nucleosides were assayed against several viruses and tumors such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…Our group, however, has shown that deletion of NF-nB (p65) abolishes the TNF-induced expression of COX-2 and cyclin D1 (46), indicating the critical requirement of NF-nB in the expression of these genes. The suppression of expression of various NF-nB regulated gene products examined here may explain the antitumor and antiviral properties of recently synthesized analogues of pinitol (7,47). We also found that this inositol potentiated the apoptotic effects of TNF and chemotherapeutic agents.…”
Section: Discussionsupporting
confidence: 61%
“…Our group, however, has shown that deletion of NF-nB (p65) abolishes the TNF-induced expression of COX-2 and cyclin D1 (46), indicating the critical requirement of NF-nB in the expression of these genes. The suppression of expression of various NF-nB regulated gene products examined here may explain the antitumor and antiviral properties of recently synthesized analogues of pinitol (7,47). We also found that this inositol potentiated the apoptotic effects of TNF and chemotherapeutic agents.…”
Section: Discussionsupporting
confidence: 61%